Relationship between Nutrition Intake and Hemoglobin Levels in Toddlers Aged 12-24 Months - Triastika Ayu Nurjannah; Fardila Elba; Sefita Aryuti Nirmala; Ariyati Mandiri; Merry Wijaya (Althea Medical Journal, 2021)
Background: The toddler period is a crucial life period and needs special attention. Toddlers need to have a proper amount and good quality of nutrition from daily food to prevent anemia. This study aimed to explore the relationship between nutritional intake and Hb level in toddlers aged 12-24 months in Sumedang District, West Java, IndonesiaMethods: This was a cross-sectional quantitative conducted in August-November 2019 on 96 toddlers aged 12-24 months. Toddlers were recruited using proportioned simple random sampling method. The mothers of these toddlers were asked to complete a food record for three consecutive days for their toddlers. Data were then processed using the Nutrisurvey application while the hemoglobin (Hb) level was measured using a Digital Hb tool. All data were analyzed using a Pearson Correlation Test.Results: Most mothers of these toddlers graduated from senior high school (45.8%) and were housewives (78.1%). The iron requirement was met 61 toddlers (63.5%). Most toddlers were not anemic (56.3%) with a mean Hb of 10.99 gr/dl. A relationship was established between iron intake and Hb level (p=0.000).Conclusion: Low iron intake is associated with Hb level in toddlers aged 12-24 months in Sumedang District, West Java Province, Indonesia. A nutrition program needs to be well set-up for toddlers in this area.